Clinical and Histopathological Evaluation of Benign Vocal Cord Lesions: A Prospective Study at a Tertiary Care Hospital (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Benign vocal cord lesions, including nodules, polyps, papillomas, Reinke’s edema, and cysts, commonly cause voice changes and sometimes respiratory distress. Polyps and nodules are frequent in adults due to prolonged voice use while children may develop recurrent respiratory papillomatosis (RRP) from HPV. Occupational voice use and irritant exposure increase risk. Objective: To assess the clinical features, histopathology, and treatment outcomes of benign vocal cord lesions in a tertiary level Medical College Hospital. Methods: A prospective study was conducted at Jahurul Islam Medical College and Hospital from January 2017 to January 2019. Twenty symptomatic patients with laryngeal lesions were included. Detailed history, ENT examination, indirect and fibreoptic laryngoscopy were performed. Demographic, occupational and habit-related data were recorded. All lesions were managed surgically when indicated and histopathological evaluation was performed. Results: Out of 20 patients, 14 were male and 6 female, with a mean age of 25.5±12.9 years. Polypoidal lesions were most common (60%), equally affecting right and left vocal cords. Nodules accounted for 25%, papillomatosis for 15%, and papilloma for 5%. Lesions predominantly involved the free margin of the vocal cords (65%), with bilateral involvement in 45% of cases. High-risk occupations included teachers, religious leaders, singers and drivers. Conclusion: Benign vocal cord lesions, mainly polyps and nodules, commonly affect males with high vocal demands. Surgical excision via direct laryngoscopy is effective, though pediatric RRP may need multiple procedures.JAFMC Bangladesh, Vol 21, No 2 (December) 2025:36-39